The impact of a sedental lifestyle and excessive screen time on postural disorders and musculoskeletal pain in adolescents: a multicenter study - Nahorniak, Mykhailo (Global Prosperity, 2025)
With the increasing digitalization of education and leisure, the need to study the impact of a sedentary lifestyle on the health of adolescents is becoming increasingly urgent. The increasing use of digital tools for educational and leisure purposes has led to several changes in the habits of young people. As a result, posture disorders and musculoskeletal pain have become a medical condition not only in pediatric medicine but also in society at large. The increase in time spent sitting in front of gadget screens is associated with posture disorders and an increase in the frequency of musculoskeletal pain. These are the main factors that cause the most concern in young people who are changing and vulnerable to external factors. Thus, the study investigated the relationship between sitting, screen time, and physical illness in adolescents. This article, in turn, reveals the results of a series of studies focused on understanding the effects of a sedentary lifestyle, especially excessive use of electronic devices, on the adolescent body. The study focused on online articles that addressed how screen time affects the amount of physical exercise of children of both sexes aged 10-17 years. A statistical evaluation of the results was performed to confirm their reliability. More specifically, the Pearson parameters and the significance of the results were determined. The data are consistent with the fact that avoiding screen time for the most extended duration can decrease the likelihood of back and neck pain only if adequate physical activity is provided in the school environment. The study results show that, for the most part, a statistically significant correlation was observed in most girls. The period of sedentary behaviour was long, so the number of musculoskeletal pain was also significantly higher (p < 0.01). At the same time, a similar case was observed in boys but less pronounced (p = 0.092). The study showed that young people who spent excessive time in front of a screen (more than 4 hours per day) were most likely to believe that their posture was incorrect and to experience back muscle fatigue and neck discomfort. The results illustrate the need to combine posture reduction and digital hygiene schemes in schools with the creation of interdisciplinary interventions to eradicate poor posture and chronic musculoskeletal pain in young people.